2005
DOI: 10.1136/jmg.2004.020446
|View full text |Cite
|
Sign up to set email alerts
|

Complete allelic analysis of BRCA1 and BRCA2 variants in young Nigerian breast cancer patients

Abstract: ). Only 5-10% of breast cancers are associated with mutations in the susceptibility genes BRCA1 and BRCA2. However, in cases associated with strong family history, mutation rates are higher, ranging from 16% to 26% for BRCA1 [1][2][3] and from 7% to 13% for BRCA2.2 3 However, many breast cancer patients with strong family histories have no obvious mutations in BRCA1/2. While there is an active search for other breast cancer susceptibility genes, it is possible that the true contributions of BRCA1 and BRCA2 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…This variant has been found in many individuals with a family history of breast cancer and has been classified as a variant of no clinical significance in the Breast Cancer Information Core Database (BIC) [16]. On the other hand, in silico prediction methods suggest that this is a nontolerated amino acid substitution within the limits of confidence in the alignments [17]. Therefore, until functional data become available, the pathogenicity of this variant cannot be excluded, and it may be a variant that increases risk moderately, but is indeed, not highly penetrant.…”
Section: Discussionmentioning
confidence: 99%
“…This variant has been found in many individuals with a family history of breast cancer and has been classified as a variant of no clinical significance in the Breast Cancer Information Core Database (BIC) [16]. On the other hand, in silico prediction methods suggest that this is a nontolerated amino acid substitution within the limits of confidence in the alignments [17]. Therefore, until functional data become available, the pathogenicity of this variant cannot be excluded, and it may be a variant that increases risk moderately, but is indeed, not highly penetrant.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 1 large series of high-risk patients estimated a similar prevalence in patients of African or European ancestry. 12 Other studies in African American women 12,[25][26][27][28][29][30][31][32] or Nigerian women 33,34 did not include other racial/ethnic groups for direct comparison.…”
Section: Commentmentioning
confidence: 99%
“…4,6 Mutation rates are higher in patients with a strong family history ranging from 16-26% in BRCA 1 and 7-13% in BRCA 2. 4 In patients with BRCA 1 mutation, there is a 50% chance of developing breast cancer by age 50, and an 80% chance by 70 years of age. 13 The lifetime risk for ovarian cancer in these patients is 1 in 2.…”
Section: Genetic Factors and Early Onset Cancermentioning
confidence: 99%
“…Fackenthal et al analysed 39 young Nigerian breast cancer patients and found that 74% carried at least one BRCA 1 and 2 variation with 69% having sequence variation in BRCA 2, representing a higher frequency of BRCA 2 variants compared to a previously studied white cohort. 4 It is proposed that the significant genetic variation in BRCA 1 and 2 may contribute to breast cancer risk. No founder mutation was identified in this study.…”
Section: Genetic Factors and Early Onset Cancermentioning
confidence: 99%
See 1 more Smart Citation